Shadow Filters Using Multiple-Input Differential Difference Transconductance Amplifiers - Kumngern, Montree; Khateb, Fabian; Kulej, Tomasz (My University, 2023)
This paper presents new voltage-mode shadow filters employing a low-power multiple-input differential difference transconductance amplifier (MI-DDTA). This device provides multiple-input voltage-mode arithmetic operation capability, electronic tuning ability, high-input and low-output impedances. Therefore, the proposed shadow filters offer circuit simplicity, minimum number of active and passive elements, electronic control of the natural frequency and the quality factor, and high-input and low-output impedances. The proposed MI-DDTA can work with supply voltage of ±0.5 V and consumes 9.94 μW of power. The MI-DDTA and shadow filters have been designed and simulated with the SPICE program using 0.18 μm CMOS process parameters to validate the functionality and workability of the new circuits.
Keywords: analog filter; differential difference transconductance amplifier; multiple-input MOS technique; shadow filter